CD73-Adenosine A1R Axis Regulates the Activation and Apoptosis of Hepatic Stellate Cells Through the PLC-IP3-Ca2+/DAG-PKC Signaling Pathway - Liu, Zhenni; Wu, Xue; Wang, Qi; Li, Zixuan; Liu, Xueqi; Sheng, Xiaodong; Zhu, Hong; Zhang, Mengda; Xu, Junrui; Feng, Xiaowen; Wu, Baoming; Lv, Xiongwen (Frontiers in Pharmacology, 2022)
Alcohol-related liver fibrosis (ALF) is a form of alcohol-related liver disease (ALD) that generally occurs in response to heavy long-term drinking. Ecto-5′-nucleotidase (NT5E), also known as CD73, is a cytomembrane protein linked to the cell membrane via a GPI anchor that regulates the conversion of extracellular ATP to adenosine. Adenosine and its receptors are important regulators of the cellular response. Previous studies showed that CD73 and adenosine A1 receptor (A1R) were important in alcohol-related liver disease, however the exact mechanism is unclear. The aim of this study was to elucidate the role and mechanism of the CD73-A1R axis in both a murine model of alcohol and carbon tetrachloride (CCl4) induced ALF and in an in vitro model of fibrosis induced by acetaldehyde. The degree of liver injury was determined by measuring serum AST and ALT levels, H & E staining, and Masson’s trichrome staining. The expression levels of fibrosis indicators and PLC-IP3-Ca2+/DAG-PKC signaling pathway were detected by quantitative real-time PCR, western blotting, ELISA, and calcium assay. Hepatic stellate cell (HSC) apoptosis was detected using the Annexin V-FITC/PI cell apoptosis detection kit. Knockdown of CD73 significantly attenuated the accumulation of α-SMA and COL1a1 damaged the histological architecture of the mouse liver induced by alcohol and CCl4. In vitro, CD73 inhibition attenuated acetaldehyde-induced fibrosis and downregulated A1R expression in HSC-T6 cells. Inhibition of CD73/A1R downregulated the expression of the PLC-IP3-Ca2+/DAG-PKC signaling pathway. In addition, silencing of CD73/A1R promoted apoptosis in HSC-T6 cells. In conclusion, the CD73-A1R axis can regulate the activation and apoptosis of HSCs through the PLC-IP3-Ca2+/DAG-PKC signaling pathway.